Managing aggressive vertebral hemangiomas with combination therapy: a case report and literature review - Jia, Zetao; Zheng, Jianhu; Zhong, Xu; Xiu, Xin; Xie, Aokang; Liu, Guoyan; Chen, Yungang (Frontiers in Oncology, 2025)
Vertebral hemangiomas (VH), the most prevalent benign spinal tumors, often remain asymptomatic for many years or even a lifetime. Symptomatic cases are rare, constituting only 0.9%–1.2% of cases. Approximately 55% of symptomatic VH cases present with pain as the sole manifestation, whereas the remaining 45% exhibit aggressive characteristics and are classified as aggressive vertebral hemangiomas (AVH). AVH may invade the spinal canal and/or paravertebral space, potentially causing spinal cord compression and nerve damage, thus requiring active treatment. Despite various treatment options available for AVH, a consensus on the optimal therapeutic strategy is yet to be established owing to its rarity. We report a case of AVH who presented with symptoms of spinal cord compression treated using combination therapy of preoperative arterial embolization, intraoperative vertebroplasty, and total laminectomy with spinal canal decompression. This approach was tailored to the patient’s poor physical condition and yielded satisfactory clinical outcomes at 12-month follow-up. Combination therapy maximized synergistic benefits and leveraged the advantages of each procedure, thus achieving enhanced therapeutic effects and reducing risks. Given an aging population, tailoring combination therapy for AVH to individual patient characteristics merits broader clinical adoption.